1990
DOI: 10.1182/blood.v75.10.2049.2049
|View full text |Cite
|
Sign up to set email alerts
|

Inducible production of interleukin-6 by human polymorphonuclear neutrophils: role of granulocyte-macrophage colony-stimulating factor and tumor necrosis factor-alpha

Abstract: The recent demonstration of the ability of human polymorphonuclear neutrophils (PMN) to secrete various cytokines in response to the granulocyte activator granulocyte-macrophage colony-stimulating factor (GM-CSF) but not to other cytokines, has led to the identification of PMN as biosynthetically active cells. In this study we have investigated the ability of PMN to secrete interleukin-6 (IL-6), a molecule known to be involved in inflammatory reactions. Using RNA blotting analysis and bioassays, we show that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(53 citation statements)
references
References 24 publications
1
48
1
3
Order By: Relevance
“…As can be seen in Figure 4, this coincided with an increase in IL-6 mRNA, as measured by in situ hybridization, within skeletal muscle fibers comparing PRE with POST contraction. At PRE, IL-6 mRNA was expressed peripherally at low levels around all fibers, and there was a virtual absence of IL-6 in the center of the myocytes, suggesting that, at rest, IL-6 in skeletal muscle tissue is likely to be located in cell types other than myocytes (7). However, at POST, IL-6 mRNA was selectively expressed throughout some, but not all, muscle fibers ( Fig.…”
Section: Il-6 Mrna Is Elevated After Exercise In Skeletal Muscle Fibersmentioning
confidence: 92%
“…As can be seen in Figure 4, this coincided with an increase in IL-6 mRNA, as measured by in situ hybridization, within skeletal muscle fibers comparing PRE with POST contraction. At PRE, IL-6 mRNA was expressed peripherally at low levels around all fibers, and there was a virtual absence of IL-6 in the center of the myocytes, suggesting that, at rest, IL-6 in skeletal muscle tissue is likely to be located in cell types other than myocytes (7). However, at POST, IL-6 mRNA was selectively expressed throughout some, but not all, muscle fibers ( Fig.…”
Section: Il-6 Mrna Is Elevated After Exercise In Skeletal Muscle Fibersmentioning
confidence: 92%
“…8 Secretion of IL-6 has been measured after some of the used stimuli. 6,9 Furthermore, TNF-a mRNA has been demonstrated in stimulated PMN, 10 but the measured cytokine secretion 10,11 could not be confirmed by other authors. 9 Most interesting are the results concerning IL-8, a potent stimulator of PMN.…”
Section: Introductionmentioning
confidence: 88%
“…For IL-1b, mRNA has been found in stimulated PMN 3,4 as well as cytokine production in their supernatants. 4,5 Messenger RNA for IL-6 has been obtained after stimulation of PMN 6 and even constitutively, 7 but there are also reports that it could not be detected at all. 8 Secretion of IL-6 has been measured after some of the used stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work [26][27][28][29][30][31] has shown that neutrophils can express IL-1/3 when exposed to certain pro-inflammatory stimuli. Levels of IL-1/3 mRNA were undetectable in freshly-isolated blood neutrophils ( Fig.…”
Section: Interleukin-l T~ Expressionmentioning
confidence: 99%
“…Furthermore, exposure of blood neutrophils to low concentrations of the chemotactic peptide fMet-Leu-Phe [22] or the cytokines y-interferon [23], GM-CSF [24] and G-CSF [25] results in a rapid and selective increase in gene expression. This up-regulated gene expression greatly enhances the survival of functional neutrophils and also results in the expression of several secondary cytokines such as IL-1/3, G-CSF, GM-CSF, TNF-a, a-interferon, IL-6 and IL-8 [26][27][28][29][30][31][32][33]. It is not known, however, if neutrophils express such cytokines in vivo.…”
Section: Introductionmentioning
confidence: 99%